Internet of Things Applications - from Research and Innovation to Market Deployment. - Vermesan, Ovidiu. (River Publishers, 2014)
The book aims to provide a broad overview of various topics of Internet of Things from the research, innovation and development priorities to enabling technologies, nanoelectronics, cyber physical systems, architecture, interoperability and industrial applications.